2016
DOI: 10.1136/bmjopen-2015-008119
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and mortality in the elderly: a systematic review with meta-analysis

Abstract: ObjectiveThe purpose of our study was to evaluate the association between short and long sleep duration and all-cause and cardiovascular mortality among elderly individuals.DesignSystematic review and meta-analysis of population-based cohort studies.SettingArticles were retrieved from international and national electronic databases.Study selectionStudies were identified in PubMed, EMBASE, LILACS (Latin American and Caribbean Health Sciences Literature), IBECS (Bibliographic Index on Health Sciences from Spain)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
163
4
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(188 citation statements)
references
References 79 publications
(134 reference statements)
13
163
4
8
Order By: Relevance
“…Epidemiological studies usually defined self-reported short and long sleep duration as less than 6 or 7 hours per day and more than 8 or 9 hours per day, respectively. 26,[29][30][31] Some researchers suggested 7 to 8 hours per day as appropriate for the university students, whereas fewer than 7 hours is defined as short sleep and more than 8 hours is regarded as long sleep. 32,33 The National Sleep Foundation has recommended 7 to 9 hours per day as the appropriate sleep duration for young adults.…”
Section: Sleep Duration and Sleep Patterns In Chinese University Studmentioning
confidence: 99%
“…Epidemiological studies usually defined self-reported short and long sleep duration as less than 6 or 7 hours per day and more than 8 or 9 hours per day, respectively. 26,[29][30][31] Some researchers suggested 7 to 8 hours per day as appropriate for the university students, whereas fewer than 7 hours is defined as short sleep and more than 8 hours is regarded as long sleep. 32,33 The National Sleep Foundation has recommended 7 to 9 hours per day as the appropriate sleep duration for young adults.…”
Section: Sleep Duration and Sleep Patterns In Chinese University Studmentioning
confidence: 99%
“…Several systematic reviews on sleep duration and mortality have found that the optimal sleep duration is 7 hours, with a significant increase of overall mortality for individuals with short (≤6 hours) or long (≥8 hours) sleep. [1][2][3] In a critical review, Kurina et al 4 argue that results from the literature are not totally consistent. The analysis of Kurina et al included 42 studies and only 14 of these showed a U-shaped relationship, while 23 studies (43%) showed no association at all, and the remainder showed associations for either short or long sleep.…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated in recent years that besides the traditional elements of lifestyle such as diet and physical activity, an additional factor, namely sleep, is involved in metabolic processes, hormonal functions, and energy homeostasis [1]. Tests have shown that sleep duration is associated with adverse health outcomes, such as obesity [2,3], type 2 diabetes [3][4][5], cardiovascular disease [3,6], and allcause mortality [7,8]. Inadequate sleep duration may also be a risk factor of metabolic syndrome (MetS) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%